Implementasi Knowledge Management pada Perancangan Website Panduan Perusahaan menggunakan Framework Laravel - Arimbawa, Nicolaus Ardy Yoga; Edi, Sri Winarso Martyas (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Onboarding is crucial to help new employees quickly adapt, understand their tasks, and become productive. This research addresses onboarding issues in the IT Service & Business Partner department of PT. Pupuk Kalimantan Timur, particularly for Non-Organic Workers (TKNO), which are currently unstructured and inefficient. The proposed solution is implementing knowledge management through a Laravel-based guide website that provides clear and structured guidelines, enabling self-learning and access to information anytime. Two phases from the 10-step knowledge management roadmap are used to complete the research: infrastructure evaluation, and knowledge management design & development analysis. The prototyping method was used in system development, including problem identification, implementation, testing, and evaluation. Results show that this website improves orientation efficiency and facilitates information delivery. BlackBox testing confirms all features function as expected, making this system likely to facilitate onboarding and knowledge transfer within the company.